The Macroeconomic Impacts of Digitalization in Sub-Saharan Africa : Evidence from Submarine Cables - Simione, Felix (IMF Working Papers; Working Paper ;, 2021)
The Macroeconomic Impacts of Digitalization in Sub-Saharan Africa: Evidence from Submarine Cables.